2014
DOI: 10.2478/s13382-014-0281-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sauna bathing on lipid profile in young, physically active, male subjects

Abstract: Objectives: The aim of the study was to evaluate effects of Finnish sauna bathing on lipid profile in healthy, young men. Material and Methods: Sixteen male subjects (20-23 years) were subjected to 10 sauna bathing sessions in a Finnish sauna every 1 or 2 days. The mean sauna temperature was 90±2°C, while humidity was 5-16%. Each session consisted of three 15-minute parts and a 2-minute cool-down between them. The following measurements were taken before and after the sauna sessions: body mass, heart rate, bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
(32 reference statements)
2
32
0
2
Order By: Relevance
“…Evidence suggests that the responses produced by an ordinary sauna bath correspond to those produced by moderateor high-intensity physical activity such as walking. 32 Pathways implicated in the effects of sauna bathing on vascular disease and mortality risk include reduction in systemic BP 14 ; improvement in endothelial function [33][34][35] ; reduction in oxidative stress 36,37 and inflammation 38,39 ; beneficial modulation of the autonomic nervous system 11 ; positive alteration in levels of circulating vascular risk factors such as natriuretic peptides 40 and lipids 41,42 ; hormonal changes; improved arterial stiffness, arterial compliance, and intima media thickness 7,36,40,43,44 ; and improvement in the cardiorespiratory system 45 as well as cardiovascular function 3,4,46 (Figure 2). Indeed, these pathways are involved in the pathophysiology of chronic disease outcomes such as type 2 diabetes and CVD as well as mortality.…”
Section: Pathways Implicated In Health Benefits Of Sauna Bathingmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that the responses produced by an ordinary sauna bath correspond to those produced by moderateor high-intensity physical activity such as walking. 32 Pathways implicated in the effects of sauna bathing on vascular disease and mortality risk include reduction in systemic BP 14 ; improvement in endothelial function [33][34][35] ; reduction in oxidative stress 36,37 and inflammation 38,39 ; beneficial modulation of the autonomic nervous system 11 ; positive alteration in levels of circulating vascular risk factors such as natriuretic peptides 40 and lipids 41,42 ; hormonal changes; improved arterial stiffness, arterial compliance, and intima media thickness 7,36,40,43,44 ; and improvement in the cardiorespiratory system 45 as well as cardiovascular function 3,4,46 (Figure 2). Indeed, these pathways are involved in the pathophysiology of chronic disease outcomes such as type 2 diabetes and CVD as well as mortality.…”
Section: Pathways Implicated In Health Benefits Of Sauna Bathingmentioning
confidence: 99%
“…Finnish sauna baths have also been found to positively modulate circulating levels of lipids such as total cholesterol, low-density lipoprotein cholesterol, highdensity lipoprotein cholesterol, and triglycerides. 41,42 There is also evidence that sauna exposure could boost the immune system, 51 which may partly explain why sauna baths reduce susceptibility to common colds and prevent infections in healthy individuals. 24 Furthermore, the effects of sauna bathing on vascular and nonvascular diseases may in part be mediated via reduced oxidative stress, as oxidative processes are known to be involved in the etiology of several disease conditions.…”
Section: Pathways Implicated In Health Benefits Of Sauna Bathingmentioning
confidence: 99%
“…Indeed, in two studies that evaluated the effect of Finnish sauna bathing on lipid profile, there were significant decreases in total cholesterol and LDL cholesterol after 2–3 weeks of sauna exposure [37, 38]. One study suggested that the lipid changes as a result of sauna exposure were similar to that produced by moderate-intensity physical exercise [37]. We have also previously shown that long-term sauna exposure is associated with reduction in levels of markers of inflammation [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…), total cholesterol and LDL cholesterol (Gryka et al . ) have been shown to decrease with heat therapy. Populations that have a limited ability to perform aerobic exercise could potentially benefit from this treatment.…”
mentioning
confidence: 99%
“…Few treatment modalities are as widely accessible, safe in both the general (Kukkonen-Harjula et al 2006) and disease (Basford et al 2009) populations, and cost effective as heat therapy. Moreover, other markers of disease such as glycated haemoglobin (Krause et al 2015), total cholesterol and LDL cholesterol (Gryka et al 2014) have been shown to decrease with heat therapy. Populations that have a limited ability to perform aerobic exercise could potentially benefit from this treatment.…”
mentioning
confidence: 99%